واقع الإستثمار الأجنبي المباشر في الجزائر في ظل تداعيات جائحة Covid 19 - بن خالدي, نوال (جامعة الوادي - University of Eloued, 2022)
This study aims to analyze the reality of foreign direct investment in Algeria in the presence of the repercussions of the Covid19 pandemic. We address the reality of the investment climate in this country by analyzing the volume of foreign direct investment in Algeria, and how these flows have been affected by the Covid19 pandemic. We have achieved a number of results, the most important of which is that the hydrocarbon sector is the most attractive in attracting foreign investors. However, the volume of investments in Algeria has decreased significantly due to the health conditions in all countries of the world.
The reality of foreign direct investment in Algeria under the repercussions of the Covid19 pandemic
مقال
Keywords: الاستثمار الأجنبي المباشر ; جائحة Covid19 ; مناخ الإستثمار ; الجزائر ; مؤشر الشفافية